Do Domestic Firms Benefit from Direct Foreign Investment? Evidence from Venezuela - Aitken, Brian J; Harrison, Ann E (American Economic Review, 1999)
Governments often promote inward foreign investment to encourage technology “spillovers” from foreign to domestic firms. Using panel data on Venezuelan plants, we find that foreign equity participation is positively correlated with plant productivity (the “own-plant” effect), but this relationship is only robust for small enterprises. We then test for spillovers from joint ventures to plants with no foreign investment. Foreign investment negatively affects the productivity of domestically owned plants. The net impact of foreign investment, taking into account these two offsetting effects, is quite small. The gains from foreign investment appear to be entirely captured by joint ventures. (JEL F2, O1, O3).